Floral biology and phenological overlap of angiosperms from a flooded forest, lake Maracaibo basin, Venezuela - Barrios Orozco, Yeni Celeste; Ramírez, Nelson (Instituto de Ecología, A.C., 2020)
Abstract: Background and Aims: Floral biology in tropical communities under seasonal climate has shown a preponderance of floral characters related with generalist pollination. In this context, we described the floral biology of 48 species from a seasonally flooded community with the aim of exploring the relationship between floral traits, examining the diversity of pollination syndromes and evaluating the effectiveness of this concept to predict pollinator classes. The overlap of flowering periods of species with the same pollination syndromes and/or pollinator classes was also explored in order to look for a pattern that could reflect the adverse effects of the pollinators overlap. Methods: The sexual system, dichogamy and/or hercogamy, type of pollination unit, dimensions, form, symmetry and spatial orientation of the flower, floral attractants and rewards, time of anthesis, floral longevity, pollination syndromes and pollinator classes were described for each species. Interspecific overlap was estimated using Pianka’s index, and then contrasted with randomly generated values. Key results: Most species were hermaphrodite, adichogamous and not hercogamous; showed individual pollination units, with small dimensions, open forms, radial symmetry, horizontal orientation, white color, and nectar as the principal reward. Flowers showed mainly diurnal anthesis and short longevity, generally of one day. Melittophily was the predominant pollination syndrome and bees were the principal class of pollinators, even though many species were pollinated by more than one type of agent. Temporal distribution of flowering periods did not differ from what is expected from a random arrangement. Conclusions: The results allow us to conclude that beyond predictions from floral syndromes, in the community prevails a polyphilic system that possibly results in greater pollination opportunities for plant species.